The short- and long-run determinants of less-educated immigration into US states - Nicole B. Simpson; Chad Sparber (Institute for the Study of Labor (IZA), 2012)
This paper uses a gravity model of migration to analyze how income differentials affect the flow of immigrants into U.S. states using annual data from the American Community Survey. We add to existing literature by decomposing income differentials into short- and long-term components and by focusing on newly arrived less-educated immigrants between 2000-2009. Our sample is unique in that 95 percent of our observed immigrant flows equal zero. We accommodate for the zeros by using scaled ordinary least squares, a threshold tobit model from Eaton and Tamura (1994), and the two-part model to analyze the determinants of immigration. Models that include observations with zero flow values find that recent male immigrants respond to differences in (short-term) GDP fluctuations between origin countries and U.S. states, and perhaps to (long-term) trend GDP differences as well. More specifically, short-run GDP fluctuations pull less-educated male immigrants into certain U.S. states, whereas GDP trends push less-educated male immigrants out of their countries of origin. Effects for less-educated women are less robust, as GDP coefficient magnitudes tend to be much smaller than in regressions for men.
urn:nbn:de:101:1-201207125862
Keywords: J61; E01; 330; immigration; macroeconomics; GDP; gravity; Einwanderung; Ungelernte Arbeitskräfte; Einkommen; Teilstaat; Sozialprodukt; Konjunktur; USA